Building in Children a Sense of "Love for the Motherland" Based on the Singkil Tribe Community's Traditional Wisdom in Southeast Aceh in the Covid-19 Era - Muhammad Shaleh Assingkily; Noni Putri (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
Character education is an important value for education in elementary age children. Typically, the principles of character are taught in classrooms by teachers to students, which is different from the Covid-19 period. This paper analyzes the local wisdom of the Singkil migrant community in Southeast Aceh who provide education to children to love their homeland. This was done as an effort to avoid lost generation during the Covid-19 pandemic. Data were collected using in-depth interviews and participant observation, plus documentation review. Furthermore, the data were analyzed through reduction, display and conclusion techniques. Then, its validity was tested through triangulation techniques and member checks. The results of this study indicate that (1) local wisdom of the Singkil community includes dampeng dance, handkerchief dance, tawakh flour and wooden canang games; (2) through local wisdom, it can foster a love of the motherland character in children, marked by habituation and habituation for children; and (3) through local wisdom, it can avoid lost generation in the Covid-19 era, marked by cognition education and inculcation of values given to children even though studying in the outdoors.